KETIDAKSESUAIAN METODE MENGAJAR GURU DENGAN TAHAP PERKEMBANGAN MEMBACA SISWA KELAS I SEKOLAH DASAR - Dhea Amanda Alfa Rezki; Annisa Humaila; Zhafira Sayyidatunnisa (STKIP Subang, 2026)
This study aims to describe the mismatch between teachers' teaching methods and the reading development stages of first-grade students at SDN 80/I Muara Bulian. The background of this research is the identified reading instruction practices that do not consider the cognitive and linguistic developmental characteristics of children aged 6–7 years. This study employs a qualitative approach with a descriptive method. Data were collected through non-participant observation of the reading learning process in first grade across several naturally occurring learning sessions. Data were analyzed descriptively by identifying observed learning practices and relating them to relevant theories and prior research findings. The results indicate that the teacher uses a combination of methods, namely spelling letters on the blackboard, reading aloud together, and using textbooks without adequate sequencing. This combination of methods is not fully aligned with the reading development stages of first-grade students, as it is not preceded by phonological awareness strengthening and lacks the use of multisensory media. Student conditions in the classroom vary: some experience difficulties, some appear unfocused, and only a small portion are actively participating in the lesson. This mismatch is influenced by limited teacher understanding of early literacy, pressure to complete the curriculum, and a shortage of age-appropriate learning media in the classroom. These conditions reflect a considerable gap between classroom practice and the principles of literacy development supported by empirical research. This study recommends the use of systematic phonics methods, contextual SAS methods, and learning media that engage more of children's learning modalities. The implementation of differentiated instruction is also necessary to address the diverse reading abilities of first-grade students.